Musikalische Motive bei Andrej Platonov. Eine diachronische Untersuchung - Günther, Hans (Wiener Slawistischer Almanach, 2022)
In my paper I examine the development of musical (including acoustic) motifs in Andrei Platonov´s works from the early 1920s until the mid-1930s. In music, as well as in many other fields, Platonov proves to be extremely sensitive to the change of the cultural atmosphere in Soviet Russia. That is why the function of the musical motifs in his works is closely connected with the changing social context. In my investigation, I focus on examples which are, broadly speaking, characteristic of three stages of development Firstly, the opposition of folk music and the “music of the machine” which was typical for the early proletarian culture (exemplified by a variety of texts from 1918–1925); secondly, the gradual replacement of the folk tradition by Soviet music (Čevengur/Tchevengur, Sharmanka / The Street-Barrel); thirdly, motifs connected with the relationship of an individual musician with the social surroundings and the official demand for narodnost´ in the 1930s (“Moskovskaia skripka” / “The Moscow Violin”, “L′ubov′ k Rodine, ili Puteshestvie vorob′ia” / “The Love of the Native Country, or the Journey of a Sparrow”).